Effect of Leaf Water Potential on Internal Humidity and CO2 Dissolution: Reverse Transpiration and Improved Water Use Efficiency under Negative Pressure - Vesala, Timo; Sevanto, Sanna; Grönholm, Tiia; Salmon, Yann; Nikinmaa, Eero; Hari, Pertti; Hölttä, Teemu (Frontiers in Plant Science, 2017)
The pull of water from the soil to the leaves causes water in the transpiration stream to be under negative pressure decreasing the water potential below zero. The osmotic concentration also contributes to the decrease in leaf water potential but with much lesser extent. Thus the surface tension force is approximately balanced by a force induced by negative water potential resulting in concavely curved water-air interfaces in leaves. The lowered water potential causes a reduction in the equilibrium water vapour pressure in internal (sub-stomatal/intercellular) cavities in relation to that over water with the potential of zero, i.e. over the flat surface. The curved surface causes a reduction also in the equilibrium vapour pressure of dissolved CO2, thus enhancing its physical solubility to water. Although the water vapour reduction is acknowledged by plant physiologists its consequences for water vapour exchange at low water potential values have received very little attention. Consequences of the enhanced CO2 solubility to a leaf water-carbon budget have not been considered at all before this study. We use theoretical calculations and modelling to show how the reduction in the vapour pressures affects transpiration and carbon assimilation rates. Our results indicate that the reduction in vapour pressures of water and CO2 could enhance plant water use efficiency up to about 10 % at a leaf water potential of -2 MPa, and much more when water potential decreases further. The low water potential allows for a direct stomatal water vapour uptake from the ambient air even at sub-100 % relative humidity values. This alone could explain the observed rates of foliar water uptake by e.g. the coastal redwood in the fog belt region of coastal California provided the stomata are sufficiently open. The omission of the reduction in the water vapour pressure causes a bias in the estimates of the stomatal conductance and leaf internal CO2 concentration based on leaf gas exchange measurements. Manufactures of leaf gas exchange measurement systems should incorporate leaf water potentials in measurement set-ups.